Modified transoral carotid ultrasonography with micro-convex probe - Uchiwa, Hiroki; Iwamoto, Yoshiko; Okada, Yasushi; Kai, Hisashi; Anegawa, Takahiro; Imaizumi, Tsutomu; Yasuoka, Suguru; Aoki, Yuji; Sakima, Hirokuni; Yasaka, Masahiro; Kajimoto, Hidemi; Fukuda, Kenji (Japanese Journal of Stroke, 2013)
Background and Purpose: The aim of this study was to compare the efficacy of conventional transoral carotid ultrasonography (TOCU) using an intracavitary convex array probe and modified TOCU (mTOCU) for evaluating the far distal segment of the extracranial internal carotid artery (ICA). Methods and Results: We established mTOCU by using a micro-convex array probe. TOCU and mTOCU were performed in 5 and 7 normal volunteers, respectively. In all the subjects, the ICAs were detected easily. We found that mTOCU was superior to TOCU in the image quality. The measurements of the depth, internal diameter, and visual length of the ICA were similar in both methods. Conclusion: The evaluation of the far distal ICA would be improved by using mTOCU.